The Headmaster Ritual: The Importance of Management for School Outcomes - Anders Böhlmark; Erik Grönqvist; Jonas Vlachos (Research Institute of Industrial Economics (IFN), 2012)
The role of school principals largely resembles that of corporate managers and the leadership they provide are often viewed as a crucial component for educational success. We estimate the impact of individual principals on various schooling outcomes, by constructing a principal-school panel data set that allows us to track individual principals as they move between schools. We find that individual principals have a substantive impact on school policies, working conditions and student outcomes. Particularly, students who attend a school with a one standard deviation better principal receive on average 0.12 standard deviations higher test scores. Despite having very rich background information on principals, it is difficult to determine which principal characteristics that form the basis for successful school management. We also find a somewhat mixed picture on what management style characterizes a successful principal. We further show that the scope for principal discretion for better or for worse is larger in small schools, in voucher schools and in areas with more school competition.
Keywords: D10; I10; J10; 330; Principals; School Management